Development of Decision-making Support System to Determine the Feasibility of the Job Training Industry Using Simple Additive Weighting Method - Zubaeti, Kaisah Riski; Budianto, Aris; Maryono, Dwi (Universitas Sebelas Maret, 2017)
The activities of the job training is an activity that must be implemented at Vocational Secondary School. The lack of utilization of technology on such activities in Vocational Secondary School, so the data management of the job training become less effective and efficient. Therefore, it is necessary the information system for manage the data on the job training and produces the decision support of the decent industry of the job training as a result of the evaluation of the job training. This research has a goal to produce decision support system to determine the feasibility of the job training industry (SPK-KTP), measure the feasibility of the system, and produce a decision support using a Simple Additive Weighting (SAW) method. The information system can help the school to manage the administration on the job training, recap the daily journal, recap the reports in pursuit, and provide decision support the job training of decent industry used in the next period. SPK-KTP uses SAW method to produce decision support the job training of decent industry. SPK-KTP is the web-based information system which it is developed using the programming language PHP (Hypertext Preprocessor). This information system uses The Waterfall Model as its system development method. The steps of The Waterfall Model consists of Analysis, Design, Code, and Test. SPK-KTP has done testing to an expert of the information system with value 90,7%, an expert of the substance of the job training with value 91,6%, supervising teachers with value 83,3%, and learners with value 90,6%. Based on the result, so SPK-KTP is very decent to use.